IMPROVEMENTS IN THE PRODUCTIVE PROCESS AND MODERNIZATION THROUGH SUBSTITUTION AND CLEAN TECHNOLOGIES IN A RICE MILLING - Najar A., Carlos (2007)
The rice production includes the agriculture, productive, and distribution process. There are the need of the integral analysis, with the purpose of improve their efficient and competitively. In this contex are presented improvements that impact in the production and productivity in milling rice sited in Arequipa region. For that is making a productive process diagnostic, a benchmarking with the sector enterprises, and the introduction of more celan production concepts.